Box and Jenkins use models to predict the numbers of patients with hepatitis Alvairose in Iraq - المشهداني, ايمان محمد; كاظم, جاسم محمد (Journal of Economics and Administrative Sciences, 2016)
The time series of statistical methods mission followed in this area analysis method, Figuring certain displayed on a certain period of time and analysis we can identify the pattern and the factors affecting them and use them to predict the future of the phenomenon of values, which helps to develop a way of predicting the development of the economic development of soundThe research aims to select the best model to predict the number of infections with hepatitis Alvairose models using Box - Jenkins non-seasonal forecasting in the future.Data were collected from the Ministry of Health / Department of Health Statistics for the period (from January 2009 until December 2013) was used statistical program MINITAB16 for the analysis of time series and through differentiation standards (standard biz BIC information, standard Waikiki AIC) shows that the best model for the number of injured Alvairose liver inflammation in Iraq is a model ARIMA (1,1,0).